Pannyori Accounting Practices in the Akkorontigi Tradition: Transparency and Accountability in South Bontonompo District - Syah, Sri Rahayu; Sabaruddin, La Ode (Jati: Jurnal Akuntansi Terapan Indonesia, 2025)
This research seeks to study pannyori accounting within the Akkorontigi tradition in the community of Bontonompo Selatan District. This research uses a qualitative method with an ethnographic approach and establishes the community in the Bontonompo Selatan District as the research site. The data collection techniques include field observation, interviews with key informants, primary informants, and supporting informants, as well as documentation. Research findings: accounting practices occur when the pannyori is received by the bride's family. The practice of transparency in pannyori involves recording it, reading it aloud, and having it witnessed by the invited guests, while the practice of accountability in pannyori means returning it if the giver of pannyori holds a celebration. The meaning contained in pannyori within the Akkorontigi tradition is a form of love, a spirit of cooperation, and solidarity. Theoretical implication: expansion of the accounting concept in the sociocultural context. Policy implications: transparency in receiving, recording, and announcing (stating the amount of pannyori) and accountability in returning pannyori. With accounting practices such as accountability and transparency in the management of pannyori, the Akkorontigi tradition remains preserved and relevant in today's era, making it important to sustain.